2018
DOI: 10.3389/fpsyg.2018.01361
|View full text |Cite
|
Sign up to set email alerts
|

Are You Keeping an Eye on Me? The Influence of Competition and Cooperation on Joint Simon Task Performance

Abstract: Social interaction plays an important role in human life. While there are instances that require cooperation, there are others that force people to compete rather than to cooperate, in order to achieve certain goals. A key question is how the deployment of attention differs between cooperative and competitive situation; however, empirical investigations have yielded inconsistent results. By manipulating the (in-)dependence of individuals via performance-contingent incentives, in a visual go–nogo Simon task the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…The bodily self-other integration process (Colzato, et al, 2013 ; Liepelt et al, 2012 ) has been shown to depend on the relationship between both co-actors sharing the task (Hommel, Colzato, & van den Wildenberg, 2009 ; Iani, et al, 2011 ; Mendl, Fröber, & Dolk, 2018 ; Ruissen & de Bruijn, 2016 ; Ruys & Aarts, 2010 ). When co-actors were friendly, inviting for cooperation, their actions were more strongly integrated than actions of intimidating and unfriendly co-actors (Hommel, et al, 2009 ) indicating that self-other integration is sensitive to the social relationship between co-actors.…”
Section: Competition and Cooperation In Joint Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bodily self-other integration process (Colzato, et al, 2013 ; Liepelt et al, 2012 ) has been shown to depend on the relationship between both co-actors sharing the task (Hommel, Colzato, & van den Wildenberg, 2009 ; Iani, et al, 2011 ; Mendl, Fröber, & Dolk, 2018 ; Ruissen & de Bruijn, 2016 ; Ruys & Aarts, 2010 ). When co-actors were friendly, inviting for cooperation, their actions were more strongly integrated than actions of intimidating and unfriendly co-actors (Hommel, et al, 2009 ) indicating that self-other integration is sensitive to the social relationship between co-actors.…”
Section: Competition and Cooperation In Joint Actionmentioning
confidence: 99%
“…When performing the joint Simon task together with a person with whom the reward was shared (cooperation), the JSE was increased as compared to a situation, in which the task was played against another person (Iani, et al, 2011 ) and only the best person won the reward (competition). Combining this logic with an analysis of the sequential modulation of the JSE (Liepelt, Wenke, & Fischer, 2013 ; Liepelt, et al, 2011 ; Yamaguchi, Wall & Hommel, 2017 ), Mendl et al ( 2018 ) found the difference between cooperation and competition conditions only for actor repetition trials, not for trials in which the actor switched. This suggests that processing adjustments primarily affected the processing of one’s own actions.…”
Section: Competition and Cooperation In Joint Actionmentioning
confidence: 99%
“…As such, the task in fact becomes less social and less cooperative in nature. Because the joint Simon effect has been shown to depend strongly on cooperation vs. competition (Iani et al, 2011 ; Liepelt & Raab, 2021 ; Mendl et al, 2018 ) and is weaker in non-social vs. social situations (Dolk et al, 2013 ; Müller, Brass, et al, 2011 ; Müller, Kühn, et al, 2011 ; Stenzel et al, 2012 ), one could argue that—due to perceived social isolation—the experience of vicarious agency would diminish the joint Simon effect compared to the low agency condition. However, the low agency condition may similarly have created social distance between the co-actors, and hence may also have diminished the joint Simon effect.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, conflict adaptation denotes a reduction of the compatibility effect following incompatible trials as compared with following compatible trials (e.g., Hommel et al, 2004 ; Notebaert & Soetens, 2001 ; Ridderinkhof, 2002 ; Stürmer et al, 2002 ) and has been interpreted as increased attentional selectivity following response conflicts (Botvinick et al, 2004 ). 1 Similarly, the JSE was found to be reduced following incompatible trials both when the previous trial had been performed by oneself (go/go transitions) and even more so when it had been performed by the other (no-go/go transitions; Liepelt et al, 2013 ; Liepelt et al, 2011 ; Mendl et al, 2018 ; Yamaguchi et al, 2018 ). Because both, the action co-representation and the referential-coding accounts assume that response conflict is involved in the JSE, conflict adaptation following one’s own and following the other’s trials in the joint Simon task are in principle compatible with both accounts.…”
Section: Introductionmentioning
confidence: 97%
“…The present study aimed at testing this hypothesis. We collected data from a joint Simon task and expected to obtain a typical JSE and postconflict adjustments that were amplified following the other’s correct responses compared with following one’s own correct responses as in previous studies (Klempova & Liepelt, 2016 ; Liepelt et al, 2013 ; Liepelt et al, 2011 ; Mendl et al, 2018 ; Yamaguchi et al, 2018 ). Crucially, we expected this amplification to be weakened or abolished following the other’s correct responses if one had additionally made a commission error.…”
Section: Introductionmentioning
confidence: 99%